PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA, DAN KOMPENSASI KERJA TERHADAP TURNOVER INTENTION KARYAWAN DIRA MARKET KENCONG - Fatikasari, Dyah Ambar; Suharto, Akhmad; Winahyu, Pawestri (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Today's globalization forces companies to compete fiercely in order to survive in their business. Companies that survive are companies that have succeeded in building competitive advantages and have good performance. Human resources (HR) is one of the determinants of the company's success, because the role of human resources is to plan, implement, and control various company operational activities. The purpose of this study was to examine and analyze the effect of job satisfaction,work environment and compensation on employee turnover intention at Dira Market Kencong. This type of research is causal comparative research. The population in this study are all employees who are in the market division. The sample used was 94 respondents. The analysis tool uses multiple linear regression. The results of the study prove that job satisfaction has effect on employee turnover intention at Dira Market Kencong, work environment has effect on employee turnover intention at Dira Market Kencong, and compensation has effect on employee turnover intention at Dira Market Kencong.